Digital Technology Innovation and Enterprise Quality Development - Qin, Bingtao; Guo, Yuxi (International Journal of Global Economics and Management, 2024)
Under the background of the digital economy, digital technology innovation has become an important source for enterprises to cultivate new dynamic energy for development, but the relationship between digital technology innovation and high-quality development is still unclear. In this paper, based on the patents in the field of digital technology filed by Chinese listed companies in the manufacturing industry from 2011 to 2021, we use machine learning methods to measure the innovation index of digital technology patents, and then examine the economic impact of digital technology innovation from the perspective of the technological complexity of enterprises’ export products. It was found that digital technology innovation can significantly promote the high-quality development of export enterprises, and this conclusion is still valid after the robust type test. In terms of the impact mechanism, digital technological innovation promotes the high-quality development of export enterprises mainly through reducing administrative costs and improving labor efficiency. Further analysis reveals that digital technology innovation has a greater role in fostering larger-scale, non-state-owned, high-tech enterprises. The findings of this paper provide micro-level empirical evidence that digital technology empowers the high-quality development of enterprises, which provides a reference for improving the digitalization of enterprise trade and further promoting the construction of the Digital Strong Trade Project.